1999
DOI: 10.1007/s100960050403
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Five Chromogenic Media for Detection, Enumeration and Identification of Urinary Tract Pathogens

Abstract: Five chromogenic agar plates--CPS ID2 medium (bioMérieux, France), CHROMagar Orientation medium (Becton Dickinson, France), UriSelect3 medium (Sanofi Diagnostics Pasteur, France), Rainbow Agar UTI medium (Biolog, USA) and Chromogenic UTI medium (Oxoid, Germany)--for the detection, enumeration and direct identification of urinary tract pathogens were compared using 443 urine specimens at two hospital laboratories. The enumeration of microorganisms was consistent on the five media for 403 of the 477 (84.5%) micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
30
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 16 publications
4
30
0
Order By: Relevance
“…Several researchers - Aspell et al, (2002), Carricajo et al, (1999), and Scarparo et al, (2002), have previously demonstrated equal or superior performance of various chromogenic media over traditional media for identification of urinary tract pathogens. Table 5 shows the rate of presumptive identification of isolated organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers - Aspell et al, (2002), Carricajo et al, (1999), and Scarparo et al, (2002), have previously demonstrated equal or superior performance of various chromogenic media over traditional media for identification of urinary tract pathogens. Table 5 shows the rate of presumptive identification of isolated organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Although screening methods have been studied exhaustively, none has been universally accepted, especially for the complex microbiology of cultures from institutionalized patients (3, 17). Chromogenic agars have recently been developed to facilitate recognition of species directly on primary media (1,4,5,7,9,16,18,19,20). CHROMagar Candida (Becton Dickinson Microbiology Products [BD], Cockeysville, Md.)…”
mentioning
confidence: 99%
“…In one study, no significant differences between the isolation rates of different chromogenic media were found (2).…”
mentioning
confidence: 99%